2007
DOI: 10.1111/j.1748-1716.2006.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressed contractile reserve and impaired calcium handling of cardiac myocytes from chronically unloaded hearts are ameliorated with the administration of physiological treatment dose of T3 in rats

Abstract: These results suggest that the treatment with physiological treatment dose of thyroid hormone rescues the impaired myocyte relaxation and depressed contractile reserve at least partially through the restoration of PLB protein levels and its phosphorylation state in chronically unloaded hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…We chose 5 weeks of unloading because it has been reported that shorter periods are not associated with contractile dysfunction in normal hearts. 14,15 In contrast, other studies performed after 5 weeks of unloading demonstrated contractile dysfunction, 15,16 supporting the need for investigating the cellular mechanisms at this time-point.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…We chose 5 weeks of unloading because it has been reported that shorter periods are not associated with contractile dysfunction in normal hearts. 14,15 In contrast, other studies performed after 5 weeks of unloading demonstrated contractile dysfunction, 15,16 supporting the need for investigating the cellular mechanisms at this time-point.…”
Section: Methodsmentioning
confidence: 75%
“…Several studies have shown time-dependent changes in cardiomyocyte and papillary muscle contractile function and excitation-contraction (EC) coupling that can impair cardiac performance after prolonged unloading. [15][16][17][18] Myofilament sensitivity to Ca 2ϩ is an important determinant of cardiomyocyte contractile function and is reduced in human 19 and animal heart failure. 20 Myofilament contractile protein architecture is deranged in heart failure and partially normalized by mechanical unloading.…”
mentioning
confidence: 99%
“…handling and myocyte contractility, which were associated with the shift of MHC isozymes and altered expressions of Ca 2? cycling-related proteins [132,133]. Physiological treatment dose of TH restored the expression levels of Ca 2?…”
Section: Th and Signaling Of The Unloaded Heartmentioning
confidence: 88%
“…The transplanted (atrophic) and the orthotopic (control) hearts of the recipient animal were removed in deep anaesthesia (thiopental-sodium, 100 mg/kg body weight) 2 weeks after transplantation. An unloading period of 2 weeks was chosen to induce a stable cardiac atrophy in accordance with previous studies [12,14,40,41] while avoiding the detrimental effects of prolonged unloading on cardiac excitation-contraction coupling and contractility [21,22,29,45]. For all experiments, the orthotopic hearts served as corresponding controls.…”
Section: Animal Modelmentioning
confidence: 99%
“…Cardiac atrophy was induced in syngeneic male Lewis rats (270±5 g, n= 34, Charles River, Sulzfeld, Germany) by heterotopic abdominal heart transplantation as previously described [12,14,21,22,29,40,41,45,46]. The donor heart was harvested under deep anaesthesia (thiopental-sodium, 100 mg/kg body weight) and was transplanted into the abdominal cavity of the recipient rat under isoflurane anaesthesia (2-2.5 %).…”
Section: Animal Modelmentioning
confidence: 99%